Analisis Risiko Kegagalan Konstruksi Infrastruktur Permukiman - Dedi Suryadi; Hendrik Sulistio; Lia Amelia Megawati (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2021)
Equitable distribution of settlement infrastructure is one of the current regional government programs. However, the high budget for residential infrastructure every year is not directly proportional to the quality of the infrastructure buildings realization. Good construction project control is available for every work implementation activity, but not all construction actors can apply it correctly. Weak project control resulted in construction failure and not achieving project objectives. This study aims to analyze the most dominant risk of construction failure and respond to construction failure mitigation using the Soft System Methodology. Variables that caused construction failure were the low quality of human resources who occupy the highest rank, the quality of work that is not in accordance with specifications, inappropriate planning, low levels of supervision and a culture of contractors that have not prioritized the quality of construction work; they are factors that cause road construction and residential infrastructure failures in Bekasi Regency. The conceptual model in the form of packaging work that is tailored to the capabilities of Human Resources is one of the recommended model options, hence that work can be completed in accordance with predetermined specifications.